Processo de adaptação de trabalhadores com deficiência intelectual em trabalho competitivo com suporte natural - Sartori, Juliana Ribas (2011)
The social inclusion of people with intellectual disability becomes reality as they start occupying public spaces and do activities common to all people. In this sense, working is an important factor of social inclusion. Several legal mechanisms have been developed to help the access and permanence of people with disability into work force, such as the Quota Law and the determination of support to facilitate their adaptation. However problems related to education, prejudice and difficulty in having the necessary adjustments have been shown to be major obstacles when it comes to the fulfillment of the right of people with disability to be accepted into a job. The objective of this study was to analyze the process of adaptation of people with intellectual disability in situations of competitive labor through the use of natural support. Therefore two young people with intellectual disability were placed in competitive employment in an agricultural company, working as production assistants. Each of these young people received support from a coworker, who participated in one training to teach people with intellectual disability. Evaluations were performed before and after the training, aiming to identify changes in the work performance of colleagues in relation to teaching tasks and the impact of these changes in work performance of employees with intellectual disability. It was observed that the instructions provided by coworkers were sufficient for the employees with intellectual disability to adequately perform their work. They quickly learned and did activities with quality and skill, and showed other behaviors consistent with the work situation, such as punctuality, persistence and commitment to the activities. However, there were some behaviors that brought difficulty to their adaptation, such as social skills deficits. Some characteristics of company functioning, such as the requirement of productivity and lack of flexibility of time to adjust to the working conditions, as well as prejudice against people with intellectual disability were identified as hindering aspects of the inclusion of persons with disability in the workplace. The data obtained in this study pointed to the potential participation of colleagues in the adaptation of people with intellectual disability to work, and conducting training to make these colleagues able to play the role of coaches. It was concluded that for the inclusion of people with intellectual disability in a work situation be possible, it is necessary a larger change, involving employers, employees without disability, and persons with disability.